2019
DOI: 10.3389/fchem.2018.00676
|View full text |Cite
|
Sign up to set email alerts
|

Performance Regulation of Thieno[3,2-b]benzothiophene π-Spacer-Based D-π-A Organic Dyes for Dye-Sensitized Solar Cell Applications: Insights From Computational Study

Abstract: Dye-sensitized solar cells (DSSCs) have been widely investigated; however, the development of promising dye sensitizers is still appealing. In this work, we perform a detailed theoretical search for high-efficiency D-π-A organic dyes using density functional theory and time-dependent density functional theory calculations. Specifically, we perform geometric optimization, and electronic structure and absorption spectra calculations for isolated dyes for two thieno[3,2-b]benzothiophene π-spacer-based D-π-A organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…In addition to the research breakthrough in the experimental aspect, the theoretical calculation of quantum chemistry has also been deeply explored. Recently, Xie et al simulated the photochemical and photophysical parameters of two sensitizers with different bridging parts by theoretical means and found that the structure of the bridging part between the electron donor and the π-spacer had a great influence on the performance of the sensitizer and that the bridging part with a coplanar structure was more beneficial to the optical performance of DSSC. He and collaborators used Zn-porphyrin as a building block to explore the effect of the Zn-porphyrin insertion position on the performance of the sensitizer, and the results showed that Zn-porphyrin close to the acceptor group was more conducive to the electron transfer of DSSC and could significantly increase the short-circuit current density.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the research breakthrough in the experimental aspect, the theoretical calculation of quantum chemistry has also been deeply explored. Recently, Xie et al simulated the photochemical and photophysical parameters of two sensitizers with different bridging parts by theoretical means and found that the structure of the bridging part between the electron donor and the π-spacer had a great influence on the performance of the sensitizer and that the bridging part with a coplanar structure was more beneficial to the optical performance of DSSC. He and collaborators used Zn-porphyrin as a building block to explore the effect of the Zn-porphyrin insertion position on the performance of the sensitizer, and the results showed that Zn-porphyrin close to the acceptor group was more conducive to the electron transfer of DSSC and could significantly increase the short-circuit current density.…”
Section: Introductionmentioning
confidence: 99%
“…A high value of V OC depends on the greater difference between the bandgap energy of HOMO and LUMO by keeping the HOMO at a low energy level and LOMO at a high energy level [44][45][46][47]. The energy gap was calculated between HOMO of newly architecture cross conjugated donor molecules and LUMO of illustrious PC 61 BM acceptor material as shown in Fig.…”
Section: Dipole Momentmentioning
confidence: 99%
“…σ(λ) being the absorption cross section (in units of cm 2 /mol), obtained from the decadic extinction coefficient, ε(λ) (units of mol −1 •cm −1 ) by multiplication with 1000 cm 3 , and Γ is the number of moles of sensitizer per square centimetre of projected surface area of the film [10,77,78]. We note that the calculation of the short-circuit current density is not trivial, as the functions under the integral in Equation 6are not easily available.…”
Section: Quantities Relevant To Device Performancementioning
confidence: 99%
“…We note that the calculation of the short-circuit current density is not trivial, as the functions under the integral in Equation 6are not easily available. The solar photon flux is accessible [79] and has recently been used [78], although in other reports, the solar photon flux was approximated based on Planck's blackbody radiation approximation [80,81]. One challenge is to determine theoretically the electron injection, dye regeneration and charge collection efficiencies.…”
Section: Quantities Relevant To Device Performancementioning
confidence: 99%
See 1 more Smart Citation